Ground Target Detection in Forward Scattering Radar Using Hilbert Transform and Wavelet Techniques - Alla.H.M.H, Mohamed Khalaf (2009)
This thesis analyzed the electromagnetic signal scattered from the target crossing the Forward Scattering Radar system baseline. The aim of the analysis was to extract the Doppler signal of the target, under the influence of high ground clutter and noise interference. The scattered Doppler signal was processed by the proposed signal processing techniques to predict the existence of a target for the automatic target detection (ATD) in the FSR system. This thesis is dedicated to the detection of ground target, and for this purpose, a typical car was used as target. Two signal processing techniques, namely Hilbert Transform and Wavelet Technique, were used for target detection. The results gathered in this study showed that the detection using Hilbert Transform was only applicable for some conditions and it was used to confirm the wavelet efficiency in the detection process. Similarly, it was also found that the detection using Wavelet Technique became more robust to higher clutter and noise level. At the worst condition of the scenario, the successful detection rate is more than 75%. This good result suggest that the transmit signal can be as low as possible and open a new horizons for FSR to be applied in real applications for example in Radar Sensor Network and Microwave Fence .Two sets of field experimentations were carried out, and the target’s signal under the influence of the high clutter was successfully detected using the proposed method. Finally, an algorithm for an automatic detection of the ground target detection in FSR is proposed.